Distribution of Weedy Red Rice (Oryza sativa) Resistant to Imidazolinone Herbicides and its Relationship to Rice Cultivars and Wild Oryza Species. Issue 2 (June 2014) - Goulart, Ives C. G. R.; Borba, Tereza C. O.; Menezes, Valmir G.; Merotto, Aldo
Abstract : Several weedy red rice populations have evolved resistance to imidazolinone herbicides worldwide. The understanding of the factors related to the herbicide resistance in weedy red rice is important to prevent its occurrence in new areas where imidazolinone-resistant rice cultivars are being used, and to manage the new rice cultivars resistant to herbicides with modes of action other than the acetolactate synthase (ALS)-inhibitors that are being developed. The objectives of this study were to analyze the relationship of weedy red rice populations from southern Brazil with rice cultivars and wild Oryza species and to evaluate the occurrence of introgression from rice cultivars and seed migration as the origin of resistance to imidazolinone herbicides in weedy rice. The study was based on 27 weedy red rice populations, seven rice cultivars, and four wild Oryza species that were genotyped with 24 simple sequence repeats and three ALS -specific single-nucleotide polymorphism markers. A large proportion of the genetic variation of the weedy red rice populations was found within (74%) rather than among populations (26%). The weedy red rice populations were more closely related to the newer rice cultivars that are imidazolinone-resistant than to the older cultivars. The South American native Oryza glumaepatula and the other wild Oryza species— Oryza rufipogon, Oryza longistaminata, and Oryza glaberrima —clustered separately from weedy red rice populations, indicating a low likelihood of introgression among weedy red rice and these wild species. Seed migration was an important factor in the genetic structure of the evaluated weedy red rice populations, although gene flow by pollen from resistant cultivars was the principal reason for the spread of herbicide resistance.